TEKNIK MENGUNGKAP TAX FRAUD - Wawan Hermansyah (Jurnal Ekonomi dan Bisnis Airlangga, 2017)
Fraud is an array of irregularities and illegal act characterized by intention deception. The purpose of this study is to formulate revealed techniques of tax fraud using indirect and direct technique. 1). Indirect technique use vertical analysis, horisontal analysis, and ratio analysis technique, and 2). Direct technique use physics test. The development of this issue can be a solution for tax fraud’s problem in Indonesia. Otherwise, the study is only concerned to find sales transactions without value added tax and sales transactions that only paid a part to treasury find.This study is qualitative research with the Source of research data are balance, income statement, and cash flows statement. The method of collecting data use participation of observation. And then analysis of research data use hermeneutics.These result indicate that vertical test analysis technique and horizontal analysis technique have significant percentage and ratio analysis techniques showed indications of fraud with score M > 5,24. Besides, based on the result of physical tests showed that PT. NN less deposit the tax obligatios and hasn’t paid value added tax to treasury fund.